Effects of dietary NDF concentration on milk yield and composition in dairy goats in mid-late lactation - Cannas A.; Porcu G.; Rubattu R.; Bomboi G. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Fourteen Sarda goats in mid-late lactation were housed in individual pens where they received a common total mixed ration (TMR) during the preliminary period (21 d). During the experimental period (24 d) the goats were divided in two isoproductive groups and fed differentiated TMR: one group received a high NDF-low no fibre carbohydrate (NFC) total mixed ration (H-NDF diet = 44.7% NDF, 29.3% NFC, DM basis), while the other received a low NDF-high NFC total mixed ration (L-NDF diet = 36.9% NDF, 36.0% NFC, DM basis). These differences were achieved substituting ground corn and barley grains with beet pulp shreds and soybean hulls. Both diets contained 50% of dehydrated chopped alfalfa on a DM basis. Soybean meal completed the diets. Dry matter intake was higher in the H-NDF group, while dietary energy intake and body weight variations did not differ significantly between the two groups. Milk yield was significantly higher in the L-NDF group, while milk protein and milk urea were higher in the H-NDF group. Milk fat concentration and somatic cell count did not differ between groups, while milk fat and milk protein yields were higher in the L-NDF group. These results are in clear contrast to what was previously observed in sheep, fed diets similar to the ones used here, in which H-NDF diets induced higher milk yield than L-NDF ones.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)